Rabinal Achi : a Mayan drama of war and sacrifice - Tedlock, Dennis, 1939-2016 (OUP E-Books., 2003)
In the ancient Mayan drama Rabinal Achi, a rebel warrior is captured by the ruler of an enemy city-state and faces his certain death at court. In the dialogue that evolves the warrior dances a dance of death, makes psychic leaps to his homeland and demands a series of requests from his captors to reconcile his death far from his homeland. Tedlock presents the first direct translation from Quiche Maya to English of "Rabinal Achi". The significance of the play is great to scholars and to lay persons as a partial history, by Mayans, of their culture, and as a revelation of the ancient ritual and beliefs toward the nature of sacrifice. It is one of the few surviving pieces of Native American drama from the pre-Columbian period in the form of an intact script